2019
DOI: 10.1007/s10654-019-00589-0
|View full text |Cite
|
Sign up to set email alerts
|

Circulating total bilirubin and risk of non-alcoholic fatty liver disease in the PREVEND study: observational findings and a Mendelian randomization study

Abstract: The relationship between circulating total bilirubin and incident non-alcoholic fatty liver disease (NAFLD) is uncertain. We aimed to assess the association of total bilirubin with the risk of new-onset NAFLD and investigate any causal relevance to the association using a Mendelian randomization (MR) study. Plasma total bilirubin levels were measured at baseline in the PREVEND prospective study of 3824 participants (aged 28-75 years) without pre-existing cardiovascular disease or NAFLD. Incident NAFLD was esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Despite this evidence, the relationship between circulating total bilirubin and incident non-alcoholic fatty liver disease (NAFLD) is uncertain. Recently, two different studies were performed in China [42] and the Netherlands [43], aiming to assess the association of total bilirubin with the risk of new-onset NAFLD, and investigate the causal nature of their association using a Mendelian randomization approach. Multivariable analysis showed that elevated levels of total bilirubin were not causally associated with NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this evidence, the relationship between circulating total bilirubin and incident non-alcoholic fatty liver disease (NAFLD) is uncertain. Recently, two different studies were performed in China [42] and the Netherlands [43], aiming to assess the association of total bilirubin with the risk of new-onset NAFLD, and investigate the causal nature of their association using a Mendelian randomization approach. Multivariable analysis showed that elevated levels of total bilirubin were not causally associated with NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating bilirubin level is one robust indicator of hepatic dysfunction, and in vitro study reveals that bilirubin from jaundiced patients can inhibit the proliferative capacity of osteoblast (11,33,34). Total bilirubin has a detrimental effect on cell viability, cell differentiation and mineralization of primary human osteoblasts in a dose-dependent manner (11).…”
Section: Discussionmentioning
confidence: 99%
“…A number of prospective cohort studies have shown that DBIL levels are significantly associated with a reduction in the risk of NAFLD, providing a protective biomarker for NAFLD [ 52 ]. More importantly, this association is independent of classic risk factors including liver enzymes, coronary heart disease, Mets, diabetes, and other classic metabolic risk factors [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the relationship between TB and indirect bilirubin and the risk of NAFLD was not significant. This may be partly due to DBIL, which is more soluble in serum and acts in an active form before indirect bilirubin [ 52 , 53 ]. This conflicts with our research results.…”
Section: Discussionmentioning
confidence: 99%